Mechanistic regulation of HERV activation in tumors and implications for translational research in oncology - Cherkasova, Elena A.; Chen, Long; Childs, Richard W. (Frontiers in Cellular and Infection Microbiology, 2024)
Transcription of distinct loci of human endogenous retroviruses (HERVs) and in some cases, translation of these transcripts have been consistently observed in many types of cancer. It is still debated whether HERV activation serves as a trigger for carcinogenesis or rather occurs as a consequence of epigenetic alterations and other molecular sequelae that characterize cellular transformation. Here we review the known molecular and epigenetic mechanisms of HERV activation in cancer cells as well as its potential contribution to carcinogenesis. Further, we describe the use of HERV expression in cancer diagnostic and characterize the potential of HERV-derived antigens to serve as novel targets for cancer immunotherapy. We believe this review, which summarizes both what is known as well as unknown in this rapidly developing field, will boost interest in research on the therapeutic potential of targeting HERV elements in tumors and the impact of HERV activation in oncogenesis.